2003
DOI: 10.1093/bmb/ldg007
|View full text |Cite
|
Sign up to set email alerts
|

Near misses: a useful adjunct to maternal death enquiries

Abstract: In developed countries where maternal death is rare, the factors surrounding the death are often peculiar to the event and are not generalizable, making analysis of maternal deaths less useful. Near misses are defined as pregnant women with severe life-threatening conditions who nearly die but, with good luck or good care, survive. Incorporation of near misses into maternal death enquiries would strengthen these audits by allowing for more rapid reporting, more robust conclusions, comparisons to be made with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
203
0
28

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(236 citation statements)
references
References 13 publications
5
203
0
28
Order By: Relevance
“…4 It is now increasingly being recognised that in countries such as the UK, where maternal deaths are rare, the study of near-miss severe maternal morbidity (defined as a 'severe life-threatening obstetric complication necessitating urgent medical intervention in order to prevent likely death of the mother' 5 ) provides additional important information to aid disease prevention, treatment and service provision. 6,7 The advantages of an additional study of near-miss morbidity are several. Near-miss morbidity occurs more frequently, allowing for more rapid study completion and reporting of results owing to the larger number of cases identified.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 It is now increasingly being recognised that in countries such as the UK, where maternal deaths are rare, the study of near-miss severe maternal morbidity (defined as a 'severe life-threatening obstetric complication necessitating urgent medical intervention in order to prevent likely death of the mother' 5 ) provides additional important information to aid disease prevention, treatment and service provision. 6,7 The advantages of an additional study of near-miss morbidity are several. Near-miss morbidity occurs more frequently, allowing for more rapid study completion and reporting of results owing to the larger number of cases identified.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…Near-miss morbidity occurs more frequently, allowing for more rapid study completion and reporting of results owing to the larger number of cases identified. 6 The higher case numbers give studies of near-miss morbidity greater power to identify factors associated with disease incidence and hence generate recommendations to impact on disease prevention. 8 In addition, morbidity studies allow for the investigation of factors associated with poor disease outcomes.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…Moreover, studying what happened to them is made easier by their greater numbers and the possibility of being able to listen to them directly. [3][4][5] Although the concept of near-miss is already well-established, a consensual definition has yet to be adopted, including how the women comprising this group may be recognised. [6][7][8] Considering the potential of near-misses to contribute to the development of strategies for reducing maternal mortality, we decided to study different aspects of them using different approaches.…”
mentioning
confidence: 99%
“…In the series of this study, the MMRH was 5.73 maternal deaths from hemorrhage for each 100,000 live births, a An almost death for any complications during pregnancy, childbirth or the postpartum period, but that survived due to chance or good hospital care (20)(21) .…”
Section: Resultsmentioning
confidence: 99%